Assessment and treatment of older individuals with COVID 19 multi-system disease: Clinical and ethical implications - Lauretani, Fulvio; Ravazzoni, Giulia; Roberti, Maria Federica; Longobucco, Yari; Adorni, Elisa; Grossi, Margherita; De Iorio, Aurelio; La Porta, Umberto; Fazio, Chiara; Gallini, Elena; Federici, Raffaele; Salvi, Marco; et al. (Acta Biomedica Atenei Parmensis, 2020)
Covid-19 infection is a multisystem disease more frequent in older individuals, especially in those with multiple chronic diseases. This multimorbid and frail population requires attention and a personalized comprehensive assessment in order to avoid the occurrence of adverse outcomes. As other diseases, the COVID-19 presentation in older patients is often atypical with less severe and unspecific symptoms. These subjects both at home and during hospitalization suffer isolation and the lack of support of caregivers. The geriatric care in COVID-19 wards is often missing. The application of additional instruments would be necessary to facilitate and personalize the clinical approach, not only based on diseases but also on functional status. This narrative review starts from diagnostic evaluation, continues with adapted pharmacologic treatment and ends with the recovery phase targeting the nutrition and physical exercise. We developed a check-list of respiratory, gastro-intestinal and other less-specific symptoms, summarized in a table and easily to be filled-up by patients, nurses and general practitioners. As second step, we reported the clinical phases of this disease. Far to be considered just viral infective and respiratory, this disease is also an inflammatory and thrombotic condition with frequent bacterial over-infection. We finally considered timing and selection of treatment, which depend on the disease phase, co-administration of other drugs and require the monitoring of renal, liver and cardiac function. This underlines the role of age not just as a limitation, but also an opportunity to increase the quality and the appropriateness of multidisciplinary and multidimensional intervention in this population.